Conservative Treatment of Chronic Heart Block. Issue 5635 (4th January 1969) - Redwood, David
Abstract : A study of 203 patients with chronic heart block treated with oral long-acting isoprenaline showed that 85 (42%) were maintained satisfactorily on the drug for a mean period of 18.2 months. The survival rates at one, two, and three years were 76%, 64%, and 57% respectively. In 115 patients treatment by pacing became necessary to control symptoms, and in these patients the survival rates at one, two and three years were 83%, 72%, and 60%. The two most valuable guides to patients' response to oral isoprenaline are the response to a trial dose of intravenous isoprenaline and the type of dysrhythmia associated with their Adams-Stokes attacks. Patients with heart failure with slow ventricular rates and those with angina of effort do not respond to treatment with sympathomimetic drugs. The majority of patients with chronic heart block are elderly, and in view of the complexity of pacing systems, and the need for skilled supervision of paced patients, oral long-acting isoprenaline remains of value in the longterm management of chronic heart block, provided patients are carefully selected for this form of therapy.